Factors affecting formula compliance of infants with IgE mediated cow's milk protein allergy during the pandemic - Uygun, Dilara Kocacik; Karaatmaca, Betul; Topal, Erdem; Arga, Mustafa; Sancakli, Ozlem; Ozcan, Dilek; Igde, Mahir; Cekic, Sukru; Bingol, Gulbin; Buyuktiryaki, Betul; Sackesen, Cansin; Sursal, Alihan; et al. (Frontiers in Allergy, 2023)
Introduction Cow's milk protein allergy (CMPA) is the most commonly encountered food allergy in the world, usually seen in infants under the age of 2 years. This study aims to determine the factors including COVID-19 affecting formula compliance of CMPA patients. Methods This study is a prospective, observational study based on 10 different Paediatric Allergy-Immunology clinics in Turkey. Patients aged between 6 months and 2 years, who were followed up with IgE-mediated CMPA treatment or newly diagnosed and using breast milk and/or formula were included in the study. The sociodemographic characteristics of the patients, their symptoms, the treatments they received, and the effects of the COVID-19 pandemic on adherence to formula were evaluated with a questionnaire administered to the parents. Results The compliance rate for formula-based treatment was 30.8% (IQR: 28.3, SD: 21.86). The number of patients with a single and multiple food allergy was 127 (51.6%) and 71 (28.9%), respectively. Breastfeeding duration, daily amount of prescribed formula and addition of sweetener to the formula were found to reduce compliance (p = 0.010, p = 0.003, and p = 0.004, respectively). However, it was determined that the patient's height, weight, age at diagnosis, and age of formula onset did not have a significant effect on compliance. Conclusion It was found that the duration of breastfeeding, the increase in the daily amount of formula requirement, and the addition of sweeteners had adverse effects on formula compliance. There was no significant correlation between the formula adherence of CMPA patients and the pandemic.